Efficacy of autologous smashed follicular dermal graft and epidermal cell suspension in the treatment of chronic nonhealing trophic ulcers in Hansen's patients - M Dheemant; Harikishan Kumar Yadalla; Belliappa Pemmanda Raju (Wolters Kluwer Medknow Publications, 2021)
Context: Plantar ulcers occur in patients with leprosy not because of the disease but because of its neuropathic effects on the skin on the feet. Neuropathy increases the risk of trauma to patients' feet, leading to the development of ulcers. With the introduction of new therapeutic regimens, leprosy can now be cured. However, complications of the disease, such as sensory loss, muscle palsy, absorption of extremities, and recurrent ulcers, still lead to substantial morbidity. This short article reviews the current management of leprosy plantar ulceration in such (nonhealing chronic ulcers) patients. Aims: To evaluate the efficacy of autologous smashed follicular dermal graft and epidermal cell suspension in the treatment of chronic nonhealing trophic ulcers in Hansen's patients. Materials and Methods: A total of 23 chronic nonhealing trophic ulcers were treated with autologous smashed follicular dermal graft and epidermal cell suspension. Ulcers were assessed based on the rate of ulcer size reduction every week till 12 weeks and then once a month till the sixth month. Statistical Analysis: Analysis was done using SPSS 26 software. Independent t-test was used and a P value of <0.05 was considered statistically significant. Results: Amongst the Hansen's patients who were released from treatment, all 23 (100%) ulcers had healed within the study period of six months, and all 23 (100%) ulcers had healed within 8 weeks. Conclusion: With this modified technique of combining autologous smashed follicular dermal graft with epidermal cell suspension, trophic ulcers heal faster with good results of reepithelialization of the ulcer bed.